Teacher trainees’ perspectives of teaching graphic novels to ESL primary schoolers - Suriani Mohd Yusof,; Zalina Mohd Lazim,; Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Students in the 21st century are exposed to multimodal texts, which are texts with the combinations of the modes of prints, images, gestures and movements. Graphic novel is one of the examples of a multimodal text and this genre is introduced in the Language Arts module as part of the English language subject in the new Curriculum for Primary Schools in Malaysia. Hence, it is important that teachers should first be aware of how to make the most of multimodal texts before introducing their pupils to the strategies necessary for comprehending the text. However, without proper training on how to approach the genre, the teaching of graphic novels may pose difficulties for teachers in general and especially so for teacher trainees. This paper reports the findings of a survey conducted on teacher trainees to explore the challenges they faced in teaching graphic novels to primary schoolers. Results show that although the graphics succeeded to entice the pupils into reading the text, the teacher trainee felt that the graphics did not help their pupils in understanding the storyline. The pupils’ eagerness to go through the graphics has caused them to ignore the words in the speech balloons. Consequently this has led to incomprehensible input and misinterpretation of the content. Results from these preliminary findings can be used to further investigate the strategies good readers use to read and comprehend graphic novels, so that teacher trainee would be better prepared to utilise graphic novels in their English classes